2001
DOI: 10.1021/jf001171q
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Monoclonal Enzyme Immunoassay for the Determination of Carbofuran in Fruits and Vegetables

Abstract: The N-methylcarbamate pesticide carbofuran is a very important insecticide used worldwide. In the present work, the validation of a monoclonal antibody-based enzyme immunoassay (ELISA) to determine this compound in fruits and vegetables is described. The immunoassay is a competitive heterologous ELISA in the antibody-coated format, with an I(50) value for standards in buffer of 740 ng/L and with a dynamic range between 200 and 3100 ng/L. For recovery studies, peppers, cucumbers, strawberries, tomatoes, potatoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Although fundamentally, the ELISA results were nearly equal to the chromatographic results, or tended to somewhat overestimate theoretical values except for some imidacloprid results, when considering average recovery rates as a whole (Fig. 9), the evaluated ELISAs showed tolerable agreement with the chromatographic methods for the three pesticides, and it can be concluded that all evaluated ELISAs are practical analytical techniques that can be used as quantitative screening methods to detect pesticides in crop samples, as described in several related reports 1,8,19,28 .…”
Section: Reliability Of Elisa and Comparison Between Elisa And Convensupporting
confidence: 54%
“…Although fundamentally, the ELISA results were nearly equal to the chromatographic results, or tended to somewhat overestimate theoretical values except for some imidacloprid results, when considering average recovery rates as a whole (Fig. 9), the evaluated ELISAs showed tolerable agreement with the chromatographic methods for the three pesticides, and it can be concluded that all evaluated ELISAs are practical analytical techniques that can be used as quantitative screening methods to detect pesticides in crop samples, as described in several related reports 1,8,19,28 .…”
Section: Reliability Of Elisa and Comparison Between Elisa And Convensupporting
confidence: 54%
“…Traditionally, the analytical method for carbofuran is gas chromatography (Liska and Slobodnik 1996) and liquid chromatography with postcolumn derivatization and fluorescene detection (Barcelo 1993). Immunoassay for carbofuran based on monoclonal antibody had also been described (Abad and others 1997; Moreno and others 2001; Jin and others 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques for the determination of carbofuran have been developed including gas chromatography (GC) (Leppert, Markle, & Helt, 1983), high performance liquid chromatography (HPLC) (Nogueira, Sandra, & Sandra, 2004), liquid chromatography-mass spectrometry (LC-MS) (Honing, Barcel o, van Baar, & Brinkman, 1995;Soler et al, 2007), gas chromatography-mass spectrometer (GCeMS) (Petropoulou, Gikas, Tsarbopoulos, & Siskos, 2006), chemiluminescence (P erez-Ruiz, Martínez-Lozano, Tom as, & Martín, 2002), enzyme-linked immunosorbent assay (ELISA) (Yang et al, 2008;Moreno et al, 2001;Abad, Moreno, & Montoya, 1997;Jourdan, Ardid, Chapuy, Eschalier, & Bars, 1995), fluorimetry (Li, Zhang, Zhao, & Hu, 2010), amperometric immunosensor (Sun, Zhu, & Wang, 2011), and microcantilever sensor (Wang, Wang, Liu, & Hu, 2011). Carbofuran is thermally unstable and decomposes to the phenol under the usual gas chromatography conditions (Li ska & Slobodík, 1996).…”
Section: Introductionmentioning
confidence: 99%